PELATIHAN PEMANFAATAN FITUR CITATION DAN REFERENCE TOOLS DENGAN MICROSOFT WORD UNTUK PENULISAN KARYA ILMIAH BAGI GURU DI SMA MUHAMMADIYAH WONOSARI GUNUNG KIDUL - Muhammad Sholeh; Joko Susetyo (Publisher UPT P2M Politeknik Negeri Malang, 2017)
Referring to the Regulation of the State Minister of Administrative Reform and Reform Bureaucracy (PermenPAN) Number 16 Year 2009 on Teachers Functional Position and Ministerial Decree of the Minister of National Education and the Head of BKN Number 03 / V / PB / 2010 and Number 14 Year 2010 dated May 6, 2010 on the Implementation Guidance of Position Functional Teacher and Credit Score, one of the requirements when a teacher submits level upgrades to class III-B and above, then the teacher is required to make papers.From Teacher's side, the requirement to write a paper is an obstacle. Some objections to this requirement are that teachers should be good at dividing the time between making scientific work and the main task of teachers. Another problem is the matter of the material or ideas used in writing and the writing in the writing of scientific papers. One effort to optimize in the writing process is to utilize citation and references feature in Microsoft word. With this feature, consistency in library writing can be easily managed as long as the author is consistent in writing the library. Likewise the writing of page numbering, table of contents, list of images and table lists can be done well and consistently.In an effort to improve the competence of teachers in writing papers, community service team at the Institute of Science & Technology AKPRIND Yogyakarta provide training and mentoring teachers at SMA Muhammadiyah Wonosari Gunung Kidul. Training and mentoring is focused on citation creation material and references feature in Microsoft Word